Podoplanin expression in adamantinoma of long bones and osteofibrous dysplasia - Kashima, T; Dongre, A; Flanagan, A; Hogendoorn, P; Taylor, R; Athanasou, N (2011)
Adamantinoma of long bones (ALB) and osteofibrous dysplasia (OFD) are rare osteolytic bone tumours that principally arise in the tibia. Both ALB and OFD contain epithelial and stromal elements, as well as areas of fibro-osseous proliferation. We assessed expression of podoplanin, a glycoprotein found in osteocytes, in OFD and ALB as well as in fibrous dysplasia and metastatic cancer. Forty-two cases of ALB and OFD, 20 cases of fibrous dysplasia and 20 cases of metastatic carcinoma to bone were stained by immunohistochemistry for expression of podoplanin, epithelial (cytokeratin, epithelial membrane antigen) and vascular (CD34, LYVE-1) markers. Podoplanin was expressed in epithelial cells and tumour glands in ALB as well as in scattered intertrabecular stromal cells in both ALB and OFD. Podoplanin was not expressed by intertrabecular stromal cells in fibrous dysplasia or in metastatic adenocarcinoma. Podoplanin was expressed by osteocytes but not osteoblasts of woven and lamellar bone trabeculae in ALB, OFD, fibrous dysplasia and skeletal metastases. The finding of a common osteocyte marker in OFD/ALB stromal cells is in keeping with a close histogenetic relationship between OFD and ALB; this may reflect the prominence of fibro-osseous proliferation in these tumours. The expression of podoplanin in an osteolytic tumour of the tibia may be useful as a diagnostic discriminant in distinguishing OFD from fibrous dysplasia and ALB from metastatic adenocarcinoma. © 2011 Springer-Verlag.